Respuesta :

(3,1)(-3,-3)
slope = (-3 - 1) / (-3 - 3) = -4/-6 = 2/3

y - y1 = m(x - x1)
slope(m) = 2/3
(3,1)...x1 = 3 and y1 = 1
now we sub
y - 1 = 2/3(x - 3) <==

Answer:

[tex]y-1 = \frac{2}{3}(x-3)[/tex]

Step-by-step explanation:

To find the equation of graphed line we pick two points from the line

(3,1) and (-3,-3)

Equation of a line is y=mx+b

where 'm' is the slope and b is the y intercept

slope [tex]m= \frac{y2-y1}{x2-x1} =\frac{1+3}{3+3} = \frac{2}{3}[/tex]

we use point slope formula

y-y1= m(x-x1)

here point(x1,y1) is (3,1)  and slope m = 2/3

Plug in all the value

[tex]y-1 = \frac{2}{3} (x-3)[/tex]